Dripping dynamics of Newtonian liquids from a tilted nozzle - Taur, A.; Doshi, P.; Yeoh, Hak Koon (Elsevier, 2015)
The dripping dynamics of Newtonian liquids emanating from an inclined nozzle is studied. The fluid viscosity mu flow rate Q, nozzle radius R, and inclination angle theta have been varied independently. The drop breakup times and the different modes of dripping have been identified using high speed imaging. A phase diagram showing the transition between the dripping modes for different theta is constructed in the (We, Ka) space, where We (Weber number) measures the relative importance of inertia to surface tension force and Ka (Kapitza number) measures the relative importance of viscous to surface tension forces. At low values of We and Ka, the system shows a transition from period-1 to limit cycle before chaos. The limit cycle region narrows down with increase in inclination. Further increase in the values of We and Ka gives a direct transition from period-1 to chaos. The new experiments reveal that in the period-1 region, increasing the nozzle inclination angle theta results in lowering of the drop breakup time t(b), suggesting that the surface tension forces cannot hold the drops longer despite the weakened effective gravitational pull. This counter-intuitive finding is further corroborated by pendant drop experiments and computations. More curiously, throughout the period-1 regime, the drop volume is independent of the flow rate. This resulted in a relatively simple correlation for the dimensionless drop volume V = 1.3G(-1)Ka(0.02)(cos theta)(0.37) accurate to within 10 over wide ranges of the independent variables. (C) 2014 Elsevier Masson SAS. All rights reserved.